Exposure-based reputation mechanism promotes the evolution of cooperation. (July 2022) - Zhu, Wenqiang; Pan, Qiuhui; He, Mingfeng
Abstract: Exposure behavior can affect the reputation of both the exposer and the exposed. In this paper, we consider the effect of exposure-based reputation on the evolution of cooperation. There are three strategies in the population, including exposure cooperation, ordinary cooperation and defection. By undertaking an exposure cost, the exposer will praise the cooperator to increase his reputation and condemn the defector to decrease his reputation, while the reputation of the exposer will also change. Results show that five states emerge under different combinations of parameters, namely, all defection, all exposure cooperation, coexistence of exposure cooperation and ordinary cooperation, coexistence of exposure cooperation and defection, and coexistence of all three strategies. When the population pays moderate attention to payoff, there is a phased dominant phenomenon in three strategies regarding the temptation to defect. In addition, exposure cooperation has the opportunity to exist when the temptation to defect or the exposure cost is high. Thus, the fact that even in a harsh environment there will still be cooperators who make exposure, which provides a new perspective for understanding the emergence of cooperation. Highlights: Propose an evolutionary game model with exposure-based reputation mechanism We only focus on the changes in reputation due to exposure. Exposure cooperation has the opportunity to exist when the temptation to defect or the exposure cost is high. Three strategies have obvious phased advantages with regard to temptation to defect when pay moderate attention to payoff.